Assessment of soil seedbank composition, woody species composition and structure in olokemeji forest reserve, ogun state, nigeria. (2017)
Olokemeji forest reserve has undergone tremendous changes through anthropogenic impact on the forest ecosystem, such human impacts include farming activities, logging of wood and burning. The soil seed bank composition, woody species composition and structure were studied with a view to determine the restoration potential of the forest reserve. Six sample plots (Frequently burnt plot 1, Frequently burnt plot 2, Harvested plot, Unharvested Unburnt plot, Arable plot 1 and Arable plot 2) designated as FT1, FT2, HP, UP, AP1 and AP2 were randomly selected. Floral species identification, relative importance value (RIV), species diversity and multivariate analysis all followed standard procedures. Three replicate soil samples were collected at two different depths (0-15 cm and 15-30 cm) from each plot and they were subjected to seedling emergence for five months to determine the species composition, density and diversity of the seed banks of the six study plots. The results of seedling emergence showed that soil collected at 0-15 cm depth had a higher RIV, species diversity, individual, abundance and dominance index than soil collected at 15-30 cm depth. However, the evenness index for seedlings in the soil seed bank was considerably high across the two soil depths which depicted equal measure of spread within each study plots at both soil depths. Tectona grandis was highest in RIV. The dominance index for the woody flora was 1 in frequently burnt Plot 1 and 2 as well as Arable Plot 1 and 2 except for the Harvested Plot that had the lowest (0.29) while the . Unharvested unburnt Plot had 0.75. The diversity in Harvested Plot was low (1.54), while it was extremely low in Unharvested unburnt Plot (0.43). Trees in Unharvested unburnt Plot had the highest mean diameters at breast height, basal areas and mean heights, while the Arable Plots had lowest mean diameters at breast height, mean basal areas and mean heights.